Hubungan Masa Kerja Dan Keikutsertaan Pelatihan Dengan Keterampilan Penggunaan Alat Pemadam Api Ringan (Apar) Pada Karyawan Rumah Sakit Mandalika Nusa Tenggara Barat Tahun 2023 - Prakosa, Catur Yoga; Desimal, Iwan; Ali, Nur Aini Abdurrahman (Lembaga Publikasi Ilmiah Nusantara, 2023)
Sytem by humans as managers or occupants of the building. Many of us encounter discrepancies regarding Light Fire Extinguishers (APAR) both in how to use, place, inspect and how to maintain APAR. This had an impact on the failure of the fire extinguishing process at the start of the incident, causing a fire. The purpose of this study is to describe and analyze the relationship between working period, training participation and skills in using Light Fire Extinguishers (APAR) for Mandalika Hospital employees in 2023. This study used analytic observation with a cross-sectional method and usus an observational approach. This study uses univariate analysis and bivariate analysis. The result of the study showed that 33.8% of respondents with long working period were skilled in suing Light Fire Extinguishers while 66.2% were unskilled. Respondents with new working period were 18.4% unskilled, while 81.6% new working period were unskilled with a chi-square P = 0.087 > 0.05. It meant that there was not any relationship between working period and Light Fire Extinguishers use skills. As many as 41.3% of skilled respondents had participated in training on the use of Light Fire Extinguishers, while 58.7% were unskilled. Respondents who had never participated in training but were skilled in using APAR were 20.3% and respondents who had never participated in training were 79.7% unskilled with a chi-square value P = 0.015 < 0.05 indicating that there was a relationship between participation in training and Light Fire Extinguishers use skills.